PEMBENTUKAN KARAKTER DALAM MEMPERKUAT NASIONALISME DI KALANGAN SISWA SEKOLAH MENENGAH ATAS DI KOTA DAVAO, FILIPINA - Alif Aditya Candra; Aulia Sholichah Iman Nurchotimah; Jhon Mark Astorga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine how character formation fosters nationalism among senior high school students in Davao City, Philippines. Specifically, it explores the integration of national values within the formal curriculum, the role of school rituals and symbolic practices, the influence of teacher modeling, and the development of student agency in a multicultural context. The research employed a qualitative multiple-case study design involving 33 participants, including 24 students, 6 teachers, and 3 school administrators. Data were collected through semi-structured interviews, focus group discussions, classroom observations, and document analysis, and were analyzed using thematic analysis.The findings reveal that nationalism is fostered through the systematic integration of civic values in classroom instruction, reinforced by school rituals such as flag ceremonies and national commemorations. Teacher modeling and democratic classroom climate significantly influence students’ internalization of national values. Moreover, students demonstrate inclusive and critical forms of nationalism, particularly when engaged in participatory civic activities. However, challenges such as routine-based rituals and academic pressures may limit deeper reflection.The study concludes that effective character formation requires reflective pedagogy, inclusive practices, and meaningful civic engagement to cultivate responsible and participatory nationalism. It is recommended that schools strengthen dialogical teaching approaches and integrate experiential civic activities to enhance national identity formation.